SOME PECULIARITIES ARISING IN THE STUDY OF NONLINEAR REGRESSION USING EXCEL AND OTHER PROGRAMS - Irina Vladlenovna Orlova; Viktor Borisovich Turundaevskiy (Статистика и экономика)
The article considers the methodological and algorithmic features arising in modeling economic processes with the help of nonlinear regression models. Questions related to different approaches to estimation of nonlinear regression parameters are discussed in the article. Recommendations to build better models of non-linear regression are made.